Bi nanolines characterization by linear optical methods - Buchenko, V.V.; Goloborodko, A.A. (Functional Materials, 2016)
The present paper dedicated to experimental investigations of optical properties of Bi/Si(001) interfaces and Bi nanolines in a wide spectral range (1eV). The experimental study of optical absorption spectrum showed the widening of the optical band gap of Bi/Si(001) interfaces with increasing the bismuth coverage, whereas after nanolines formation the width of the optical band gap decreases. Features of the experimentally obtained reflectance anisotropy spectra and surface differential reflectance spectra concerned with changing of the silicon surface reconstruction from 2x1 to 1x1 with the increasing of the bismuth covering degree from 0.5 ML to 1 ML. The experimental study of reflectance anisotropy spectra and surface differential reflectance spectra of Bi nanolines shows that the bismuth atoms are still present on the surface of the substrate in small amount, but the optical properties of such structures are determined by Si dimers.